Fibrewise totally separation axioms. Issue 2 (17th February 2022) - Kadzam, Amira R.; Yousif, Y. Y.
Abstract: The purpose of this paper is to introduce and study fiberwise totally separation axioms which are generlization of separation axioms in ordinary topology called fibrewise totally T 0, (resp., T 1, R 0, Hausdorff, functionally Hausdorff, regular, completely regular, normal, and functionally normal) spaces. Also we give several propositions and examples concerning it.